Severe community pneumonia: When to think about CA-MRSA? (Actualizaciones en Sida e Infectología, 2019)
Introduction: Despite the incidence of community-acquired pneumonia (CAP) due to community acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) being less than 10%, its presence should be considered in critical patients because of its high rate of mortality.Objectives: To identify risk factors associated with CA-MRSA in patients with severe CAP.Materials and method: A retrospective, observational study analysed episodes of etiological diagnosis in patients admitted in Intensive Care Unit in a public hospital between 2006 and 2017.Results: 250 episodes of NAC were included, among which 53 were caused by SAMR-AC and 197 by other agents. Patients with MRSA were the youngest (35.6±13.4 vs 43.1±12.4, p
Keywords: Pneumonia; Community acquired pneumonia; Community acquired Staphylococcus aureus; CA-MRSA